Community Integration in Traumatic Brain Injury: The Contributing Factor of Affect Recognition Deficits. (10th June 2019) - Binder, Allison S.; Lancaster, Katie; Lengenfelder, Jean; Chiaravalloti, Nancy D.; Genova, Helen M.
Abstract: Objective: Individuals with traumatic brain injury (TBI) can experience social isolation, which is damaging to well-being and counterproductive to successful rehabilitation. It has been proposed that social cognitive deficits that commonly result from TBI may contribute to weakened social integration. However, the consequences of specific social cognitive deficits in TBI are still being delineated. The current work sought to better characterize the relationship between community integration and facial affect recognition (FAR) in TBI.Participants and Methods: A total of 27 participants with moderate to severe TBI and 30 healthy controls (HCs) completed two tests of FAR, which employed either static photographic stimuli or dynamic video stimuli (The Awareness of Social Inference Test). The Community Integration Questionnaire was also administered to participants.Results: Participants with TBI were significantly impaired on both the static and dynamic FAR measures, yet the deficits were most pronounced within the dynamic task. Furthermore, participants with TBI reported lower community integration compared with HCs. FAR was positively associated with community integration in both groups, such that participants with proficient affect recognition skills were better integrated into their communities.Conclusions: FAR deficits may contribute to the lack of community integration often observed in TBI; thus, interventions designed to improve FAR may be beneficial to this population's ability to successfully reintegrate into society.